Antibiotic exposure at environmental concentrations under high-fat diet: Impacts on gut microbiota and metabolism - Liang Zhao; Jian Xu; Xiaowei Li; Saiwa Liu; Jingjing Du; Xi Jia; Zhinan Wang; Lirui Ge; Kexin Cui; Yu Ga; Jianzhong Shen; Xi Xia (Environment International, 2025)
Antibiotics are ubiquitously present in various environments, and exposure to antibiotics at environmental concentrations is even inevitable. Here, we investigate the impact of environmentally relevant concentrations of Azithromycin (AZI) and Ciprofloxacin (CIP) on the gut microbiota and host metabolism in mice under High-Fat Diet (HFD) conditions, administered via drinking water. Long-term exposure to trace antibiotics was observed to induce significant alterations in the microbial community structure. AZI significantly altered Short-Chain Fatty Acid (SCFA) profiles, markedly increasing acetate, butyrate, and propionate production in both male and female mice. AZI and CIP significantly elevated body weight in male mice and altered serum hormones levels along with the serum metabolic profile. Moreover, antibiotic exposure significantly restructured the microbe-host interactions, encompassing both microbe-SCFA and microbe-metabolite relationships. Notably, Lactobacillus has played an essential role in shaping the overall SCFA profile in female mice exposed to AZI. Our findings indicated that exposure to trace antibiotics in conjunction with HFD elicits distinct effects on the gut microbiota and host metabolism, underscoring the need for further investigation into the potential health risks faced by susceptible populations.